2005
DOI: 10.1007/s00508-005-0330-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of labor induction on obstetric outcomes in patients with prolonged pregnancy

Abstract: Our data suggest that women undergoing labor induction because of prolonged pregnancy should be sufficiently informed regarding the risks of a cesarean section or a vacuum extraction. Furthermore, the option of elective cesarean section should be considered, particularly in primiparous women with an unfavorable cervix, higher age, and high estimated infant birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
5
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
5
5
3
Order By: Relevance
“…These results suggest that IOL has no impact on the rate of lacerations if this factor is adjusted for the effect of parity. Considering this point, our finding of a higher rate of lacerations in the IOL group does not contrast with other studies [9,11,41] which did not find any differences in that respect. Our finding of a similar risk of episiotomy after IOL is in accordance with that of other studies [41].…”
contrasting
confidence: 74%
See 2 more Smart Citations
“…These results suggest that IOL has no impact on the rate of lacerations if this factor is adjusted for the effect of parity. Considering this point, our finding of a higher rate of lacerations in the IOL group does not contrast with other studies [9,11,41] which did not find any differences in that respect. Our finding of a similar risk of episiotomy after IOL is in accordance with that of other studies [41].…”
contrasting
confidence: 74%
“…Considering this point, our finding of a higher rate of lacerations in the IOL group does not contrast with other studies [9,11,41] which did not find any differences in that respect. Our finding of a similar risk of episiotomy after IOL is in accordance with that of other studies [41]. Concerning atonic hemorrhage we found no significant differences between both groups, but we found a trend that showed a higher rate of atonic hemorrhage in the IOL group.…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…Similar nding was reported elsewhere [38]. Evidence showed that, after 42 weeks of gestation, the placenta which supplies the baby with nutrients and oxygen from the mother starts aging and eventually fails, this necessitate the IOL to facilitate delivery of the baby [39]. In addition, post-term pregnancies is related to uterine overstimulation and fetal distress.…”
Section: Discussionsupporting
confidence: 78%
“…Induction of labor is one of the most common interventions in obstetrics, being performed in approximately 15% of all pregnancies (1–3). Underlying reasons include fetal growth restriction, premature rupture of membranes, preeclampsia, intrahepatic cholestasis of pregnancy and, most commonly, post‐dates pregnancy.…”
Section: Introductionmentioning
confidence: 99%